Career development of doctorally prepared nurses - van Dongen Lisa; Hafsteinsdottir Thora B.; Broome Marion E.; Suhonen Riitta; Leino-Kilpi Helena (WILEY, 2025)
Aim: To integrate research literature regarding careers, career development and factors influencing the career development of doctorally prepared nurses.
Design: An integrative review.
Data: Sources: Medline, CINAHL and Embase were searched in June 2022 without time restrictions.
Methods: Peer-reviewed empirical publications written in English with different types of study designs were included. Two researchers independently applied eligibility criteria, selected studies and conducted quality appraisals using Joanna Briggs checklists. Data were extracted and analysed using a convergent integrated approach with thematic analysis. Themes were established within three categories based on the research questions: career, career development and factors influencing career development.
Results: Twenty-two studies were included. Nine themes were identified. One theme regarding careers describes that doctorally prepared nurses need to prioritize work within different positions. The two themes focusing on career development described the need to determine career goals after the doctorate and further develop competencies. Six themes described factors influencing career development: 'Intrinsic motivation to improve health care and nursing education', 'Available support sources', 'Professional development programmes', 'Work-life balance', 'Organizational infrastructures for career advancement' and 'Competition and hostile treatment among colleagues'.
Conclusion: Limited knowledge of the careers and career development of doctorally prepared nurses was found. Doctorally prepared nurses need to balance work with various part-time positions. Careers and career development could be supported by the development of structures for career advancement as well as supportive working environments.
Impact: Doctorally prepared nurses with strong careers are important to health care and nursing as they generate and implement new knowledge into clinical practice and thereby support the improvement of (nursing) care and patient outcomes. This study provides considerations towards strengthening the careers of doctorally prepared nurses.Reporting MethodPRISMA.Patient or Public ContributionNo Patient or Public Contribution.